Constraining an exoplanet’s magnetic field using star-planet interactions - D. Revilla; P. J. Amado; R. Luque; P. Schöfer; A. F. Lanza; A. Binnenfeld; J. A. Caballero; A. P. Hatzes; G. W. Henry; S. V. Jeffers; S. Kaur; E. Pallé; et al. (Science, 2026)
Theory predicts that a planet with a sufficiently strong magnetic field orbiting close to its host star could induce star-planet magnetic interactions. This is potentially observable as an optical or radio stellar activity signal synchronized with the planet’s orbital period. We analyzed 18 years of high-resolution optical spectroscopy of GJ 436, a low-mass star orbited by a Neptune-sized exoplanet on a polar eccentric orbit. Stellar activity indicators show enhancements at a period corresponding to the exoplanet orbit, modulated by stellar rotation, and the star’s 8-year magnetic cycle. We interpret this as a signal of star-planet magnetic interaction. Using a geometric model, we reproduced these periods if GJ 436 b has a magnetic field strength of 6 to 110 gauss.